Environmental awareness as a universal European value - Mihajlović, Ivan; Voza, Danijela; Milosevic, Isidora; Durkalic, Danijela (Serbian Journal of Management, 2016)
This issue of Serbian Journal of Management (SJM 11(2) 2016), besides containing regular research papers, is containing the papers which resulted from the International May Conference on Strategic Management - IMKSM2016 and the Students Symposium with the main topic: “Environmental awareness as a universal European Value” which was financially supported by the Visegrad Fund. The - IMKSM2016 conference was organized by Engineering Management Department (EMD) of Technical facultuy in Bor, University in Belgrade. IMKSM2016 conference was organized in Bor, Serbia, on 28-30 May 2016. The Visegrad fund project: “Environmental awareness as a universal European Value”, is listed with the following classification number 11540386.